Investigation on orthogonal frequency division multiplexing with index modulation - Fan, Rui (2016)
This thesis is devoted to investigating orthogonal frequency division multiplexing (OFDM) with index modulation (OFDM-IM) to improve its bit error rate (BER) performance and spectral efficiency. In OFDM-IM, by selecting a number of subcarriers as active subcarriers to carry constellation symbols, the indices of these active subcarriers may carry additional bits of information. Compared to classical OFDM, OFDM-IM offers spectral efficiency boost and BER performance improvement in certain circumstances. To be specific, in low SNR region, OFDM-IM's BER performance is not as good as classical OFDM's while in high SNR region, OFDM-IM outperforms classical OFDM in terms of BER performance. In addition, OFDM-IM's spectral efficiency superiority over classical OFDM is evident only when Binary Phase Shift Keying (BPSK) is adopted. For constellation sizes higher than BPSK, such superiority is only observed for very few carefully chosen system configurations. Motivated by the above analysis, this thesis focuses on improving OFDM-IM in terms of BER performance and spectral efficiency when BPSK, Quadrature Phase Shift Keying (QPSK) and constellation sizes higher than QPSK are adopted, respectively. In OFDM-IM, for a given subblock size, only a fixed number of active subcarriers are selected to carry constellation symbols, which does not make full use of other possible numbers of active subcarriers. Hence, OFDM with type-1 generalized index modulation (OFDM-GIM1) is proposed, where the number of active subcarriers in an OFDM subblock is no longer fixed. Dependent on the input binary string, different number of active subcarriers are assigned to carry constellation symbols. With the developed modulation and demodulation of indices in the OFDM-GIM1, the spectral efficiency of the scheme is further improved when BPSK is adopted. To tackle the problem of the spectral efficiency of OFDM-IM for QPSK, a novel scheme named as OFDM with type-2 generalized index modulation (OFDM-GIM2) is proposed. In this scheme, independent index modulation is performed on the in-phase and quadrature component of each subcarrier. Through such a way, a higher spectral efficiency than that of OFDM-IM may be achieved. OFDM-GIM2 may be further extended, such that the input bit string jointly decides the active indices for in-phase and quadrature components. As a result, more bits can be transmitted per OFDM frame. The symbol constellations of Phase Shift Keying (PSK) or amplitude modulation are identical when the constellation sizes are of 2 or 4. When the constellation sizes are larger, in OFDM, it is well known that Quadrature Amplitude Modulation (QAM) outperforms PSK in terms of BER performance. In this thesis, the 8PSK and 8QAM performances in OFDM-GIM1 are investigated, and the results show that OFDM-GIM1 adopting 8PSK provides a higher index detection accuracy than 8QAM, leading to a better BER performance in the low SNR region. Throughout this thesis, the implementation complexities for the proposed schemes are analyzed in respective chapters. The theoretical analysis for the index modulation systems proposed in this thesis is conducted. The mathematical demonstration of the 8PSK's superiority over 8QAM in indices detection is also detailed.